Short-term Dehydroepiandrosterone Intake and Supramaximal Exercise in Young Recreationally-trained Women - Gravisse, Nicolas; Vibarel-Rebot, Nancy; Labsy, Zakaria; Do, Manh-Cuong; Gagey, Olivier; Dubourg, Céline; Audran, Michel; Collomp, Katia (International Journal of Sports Medicine, 2018)
WADA has banned dehydroepiandrosterone (DHEA) but its ergogenic effect in female athletes has never been investigated. The aim of this study was to determine whether short-term DHEA intake would improve performance during a supramaximal field exercise in healthy young recreationally trained women. Its impact on body composition, metabolic responses was also measured. Eleven young female volunteers completed four running-based anaerobic sprint tests: just before and after treatment with either oral placebo or DHEA (100 mg/day/28days), following a double-blind and randomized protocol. Bioelectrical impedance assessed body composition. At rest and after passive recovery, blood samples were collected for lactate measurement and saliva samples for DHEA, testosterone and cortisol analysis. There was no significant difference in body composition or performance parameters after DHEA administration, despite a tendency toward increased peak power and decreased fat mass. However, DHEA treatment induced a very marked increase in saliva DHEA and testosterone concentrations (p<0.001), with no change in cortisol or lactate levels. In conclusion, short-term DHEA administration did not improve performance or have an anabolic effect in young female recreationally trained athletes, despite the increase in androgenic hormones. Further studies are needed to determine whether a higher daily dose would generate an ergogenic effect during anaerobic exercise.
Keywords: doping; DHEA; short-term administration; peak power; testosterone; body composition